Valuation model of crowdfunding campaigns applying simple additive weighting method - Santautė Venslavienė; Jekaterina Kartašova (Agora International Journal of Economical Sciences (AIJES), 2024)
Every investor has some difficulties when investing into crowdfunding campaigns, as it is not clear how to evaluate specific crowdfunding campaign or what success factors to choose. The aim of this study is to propose the crowdfunding campaign assessment model, test it empirically and illustrate how to select the most appropriate crowdfunding campaign for individual investor to invest. Multi-criteria methods, used in the evaluation process, enable to get objective answers about the effectiveness of the optimal crowdfunding campaign comprehensively by presenting some generalized indicators and considering both quantitative and qualitative data. The obtained empirical results comparing two crowdfunding campaigns show that the proposed method could be used for evaluating complex processes of the optimal crowdfunding investments, and could be adapted for various situations.
Keywords: 330; crowdfunding; crowdfunding campaign; valuation model; multi-criteria decision method; simple additive weighting